Generation and Characterization of a Mammalian Cell Line Continuously Expressing Japanese Encephalitis Virus Subviral Particles - Konishi, Eiji (American Society for Microbiology, 2001)
We have generated a cell line (F cells) producing a secreted form of Japanese encephalitis virus (JEV) subviral particle (extracellular particles [EPs]) that contains the JEV envelope glycoprotein (E) and a precursor (prM) of the virion membrane protein (M). The F cells were engineered to synthesize these JEV products from a cDNA encoding a mutated (furin proteinase resistant) form of prM, since stable cell lines expressing E and the authentic form of prM could not be obtained, due (in part) to the cell-fusing ability of EPs containing E and M. Our biochemical alteration of the prM protein was critical for the successful production of EP-producing cell lines. EPs produced by F cells share the biochemical properties of empty viral particles produced by JEV-infected cells, except that the F-cell EPs lack hemagglutinating activity and M. F-cell EPs were recognized by a panel of monoclonal antibodies to E, and EPs were shown to be useful as vaccine candidates in mice and as diagnostic reagents in evaluating human immune responses to JE vaccination. The amounts of E antigen released into the culture fluid of F cells were similar to those found in virion fractions of JEV-infected cell culture fluids or JEV-infected weanling mouse brains (the current source of antigen used to produce human vaccines for JE). Thus, the F-cell line would appear to be a useful source of antigen for JE vaccines and diagnostics.